Failure of one conductor in a nonthoracotomy implantable defibrillator lead causing inappropriate sensing and potentially ineffective shock delivery. - Epstein AE; Shepard RB (Pacing & Clinical Electrophysiology, 1993)
We describe how a single defect in a new model transvenous lead for an implantable curdioverter defibrillator can result in mal-function of the sensing and defibrillation circuits. The patient had received shocks during atrial fibrillation without premonitory symptoms. At least one shock was delivered and not fell by the patient. In addition, late in the course, a shock was delivered during atrial fibrillation documented to be with a slow ventricular response. In the transvenous lead, a distal spring functions as the anode for rate sensing and the cathode for defibrillation. The wire from this spring bifurcates near the proximal end of the catheter. One wire from the bifurcation leads to the positive (anode) rate-sensing socket of the pulse generator, and the other wire leads to the negative (cathode) high voltage output socket of the defibrillator for defibrillation and cardioversion. After the inappropriate and unperceived shocks were documented, intraoperative and postoperative electrical testing indicated that intermittent discontinuity of the distal spring system within the proximal yoke of the catheter caused faulty sensing and potentially unreliable defibrillation. This dual malfunction was possible because the distal spring of the lead functions in the high-voltage output and the rate-sensing low-voltage input circuits of the implantable defibrillator.